ANALISIS DAMPAK KELUARGA BROKEN HOME TERHADAP MINAT BELAJAR SISWA DI SMP NEGERI 1 KARANGDOWO - Mita Wulandari; Ari Prasetyoaji (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Broken home families can have a negative impact on students' interest in learning, so it is important for schools and parents to shape students' interest in learning. The purpose of this study is to provide an overview, identify the factors, and evaluate the efforts of counseling guidance teachers in increasing the learning interest of students from broken home families, with the hope of making a significant contribution to understanding the impact of broken home families on students' learning interests and offering practical recommendations. This study uses a qualitative approach, with observation, interviews and documentation as data collection techniques. The results of the study show that students with broken home backgrounds have varying learning interests as a result of individual psychological and emotional factors. Through the results of this study, it is hoped that Counseling Guidance teachers can provide emotional support, help students manage stress and internal conflicts, and provide strategies to increase learning motivation.